2017
DOI: 10.1097/dad.0000000000000910
|View full text |Cite
|
Sign up to set email alerts
|

Spiradenocarcinoma: A Comprehensive Data Review

Abstract: Suspicion of an SC should lead to performance of a magnetic resonance imaging for defining tumor extent, and a fludeoxyglucose positron emission tomography-CT for detection of metastases. Radical tumor excision and resection of tumor involved regional lymph nodes are essential for a curative approach. Histopathological evaluation should involve determination of tumor differentiation grade, because high-grade carcinomas seem to have a much more aggressive behavior. Excision of distant metastases has no therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…The case presented here is the third case. Imaging procedures, including CT scans, magnetic resonance imaging (MRI), PET-CT, chest X-ray, ultrasound, mammography and scintigraphy of the lymphatic drainage area, have been used to further define the size and extent of these primary neoplasms (26). In this case, we found a higher SUVmax (2.6) in the avid mass, while no involvement of the bony canal walls was identified (Figure 1), indicating that PET-CT is helpful in diagnosing and defining the scope of the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The case presented here is the third case. Imaging procedures, including CT scans, magnetic resonance imaging (MRI), PET-CT, chest X-ray, ultrasound, mammography and scintigraphy of the lymphatic drainage area, have been used to further define the size and extent of these primary neoplasms (26). In this case, we found a higher SUVmax (2.6) in the avid mass, while no involvement of the bony canal walls was identified (Figure 1), indicating that PET-CT is helpful in diagnosing and defining the scope of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analysis by Andreoli and Itani (27) found that sentinel node biopsy may benefit patients with clinically absent lymph node involvement before treatment. Staiger et al (26) reported that wide resection with tumor-free margins resulted in fewer recurrences and deaths due to unresected lesions (recurrence 23 vs. 43%, death 8 vs. 43%). Similarly, as early as 1997, Tay et al (33) reported recurrence rates of up to 39% if MES was left untreated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis is not entirely understood, but a defect in the tumor suppressor gene, CYLD, is thought to contribute to their development in Brooke-Spiegler syndrome, which also features multiple spiradenomas [249]. Additionally, derangements in intercellular bridge proteins that maintain epithelial organization, including claudin-4, cadherin, and beta-catenin, have also been suggested as contributing to neoplasm formation (Table 1) [250].…”
Section: Spiradenomamentioning
confidence: 99%
“…[5][6][7][8] Sex (48% female v 36% male) and age (ranging from 8 to 92 years) are not suggestive of a predisposition, although Whites (about 57%) appear to have had a higher prevalence compared with other ethnicities. 9,10 Genetically, loss of the CYLD gene, as seen in the Brooke-Spiegler syndrome, is associated with spiradenoma. 10 The product of the CYLD protein regulates the levels of NF-κB, and subjected patients with this syndrome develop a variety of skin appendage tumors.…”
Section: Introductionmentioning
confidence: 99%